Boujee Lifestyle: Irresistible Extravagance and Learning to Overcome Shopping Addiction, from an Interdisciplinary Perspective of Social Sciences and Neuroscience - Metasuk, Akara (Journal of Social Sciences Naresuan University, 2026)
This article aims to explore the phenomenon of “Boujee”, characterized by uncontrollable extravagant spending, along with consumption and shopping addiction through an interdisciplinary perspective. The objective is to comprehensively understand this phenomenon by integrating knowledge from social sciences and neuroscience, and to highlight a blended management approach within the framework of social neuroscience. Theoretical studies and literature reviews indicate that extravagant spending is rooted in social comparison, exacerbated by social stratification and inequality. Social comparison drives decision-making processes that rely on the interplay of various brain regions. However, individuals may make different decisions depending on emotional pressure, the valuation of self-image, and the internal capacity for rational judgment, in which executive functions play a crucial controlling role. Furthermore, an interdisciplinary management approach, implemented at the policy level to reduce social inequality through critical education and learning, alongside individual-level management through the cultivation of gratitude, delaying gratification, and mindfulness, may help society overcome consumption addiction in the long term, while simultaneously providing care and support for individuals in the short term.